2013
DOI: 10.1021/jp311470t
|View full text |Cite
|
Sign up to set email alerts
|

Optical and Dynamical Properties of Chemically Synthesized Gold Nanoplates

Abstract: Single crystal, micrometer-sized nanoplates were formed by reducing Au(III) in the presence of surfactants using a modified polyol protocol. The shapes of the plates range from triangular to hexagonal. The nanoplates have {111} surfaces with an average edge length of 5 ± 2 μm and an average width of 107 ± 30 nm. Scanning electron microscopy (SEM) images reveal that the plates grow through a re-entrant groove created by twinning. The optical properties of the plates were studied by scattered light and transient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 40 publications
1
67
1
1
Order By: Relevance
“…When the SPPs are excited from the middle of the bottom edge of triangular microplate, the sophisticated polarization‐dependent far‐field emission can be observed on both left‐side and right‐side edges . As shown in Figure a, the emission intensity gradually decreases with the polarization angle varying from 0° to 90° (for more details see Figure S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 94%
“…When the SPPs are excited from the middle of the bottom edge of triangular microplate, the sophisticated polarization‐dependent far‐field emission can be observed on both left‐side and right‐side edges . As shown in Figure a, the emission intensity gradually decreases with the polarization angle varying from 0° to 90° (for more details see Figure S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 94%
“…The gold nanoprism has an edge length of 950 nm and is located on a Si N 3 4 substrate (figure 2(c)). Similar nano-objects have been investigated by EELS, energy-filtered transmission electron microscopy (EFTEM) (Gu et al 2011), two-photon photoluminescence (Viarbitskaya et al 2013) and dark-field microscopy (Major et al 2013). The EELS spectrum is more complex and displays several features at 1, 1.4, 1.6 and 1.8 eV.…”
Section: Electron Energy Losses From a Generalized Field Propagatormentioning
confidence: 99%
“…15 In this context, it has recently been shown that colloidal gold platelets sustain high-order delocalized surface plasmon modes, arising from the two-dimensional (2D) confinement of the electron oscillation. [17][18][19] Indeed, multiple interferences between delocalized SPPs yield optical near-fields that are strongly localized at specific hot spots along the edges of the platelets. 17 These investigations suggest that the control of the spatial and spectral properties of the SP modes and the related SP density of states (SP-DOS) of two-dimensional metallic nanostructures could provide a tool for designing plasmonic devices for optical information processing at the nanoscale.…”
mentioning
confidence: 99%